EFFECT OF FEEDING MADE WITH DIFFERENT PROTEIN COMPOSITION ON GROWTH AND SURVIVAL RATE OF THE HUMPBACK GROUPER SEEDS (Cromileptes altivelis) - Ade Mulyana; Syafruddin Nasution; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT             The Humpback Grouper is one of the commercial marine fish that has been cultivated both for purpose of hatchery and enlargement, so that quality feed is needed for better growth. Thid research was carried on June 15- July 27, 2019 at UPTD BPBALP  Teluk Buo Kec.  Bungus, Padang City, West Sumatera Province.Providing feeding made with protein sources derived from fish head flour aims to increase the growth of the humpback grouper fish with cheaper raw materials. The method used in this research is experimental method using Completely Randomized Design (CRD) with three treatments and three replications so that it required 9 experimental units with 3 different fish head flour compositions, that is A = 26,58%, B = 31,61%, C = 36,64%. The main parameters measured include absolute length, absolute weight, specific growth rate, and survival rate of fish. While water quality parameters include temperature, pH, salinity, and dissolved oxygen. Measurement data were analyzed using Analisys of Variance (ANOVA) with α <0.05. Then proceed with the Newman Keulstest to find out where is the significance of the data and treatments that obtain optimal growth. The provision of artificial feed with different protein compositions significantly affected the growth and survival of the humpback grouper fish. Increased optimal growth was obtained in treatment C with 36,64% protein composition. Keywords: The Humpback Grouper, Fish Head Flour, Growth, Survival Rate